Model Transformasi Keamanan Digital dalam Jaringan Peer-to-Peer (P2P) untuk Efisiensi Tinggi Smart Campus - Santoso, Imam; Nursiaga, Rahmat; Quiko, Alfonso Sabatani (Universitas Teknologi Muhammadiyah Jakarta (UTM Jakarta), 2025)
Digital transformation within campus environments via Peer-to-Peer (P2P) networks and the Internet of Everything (IoE) integration offers high efficiency and intelligent connectivity, yet introduces significant network security risks. This study analyzes these risks and designs contemporary technology-based security strategies to support Smart Campus systems. Utilizing a Research and Development approach, a hybrid security model based on adaptive encryption and AI-driven monitoring was developed. Experimental results demonstrate a 72% increase in threat detection capabilities and an average attack mitigation response time of 3.4 seconds. This article proposes a digital security transformation model built upon a P2P architecture to enhance network efficiency and resilience. Furthermore, this study examines security strategies, technological innovations, and their implementation impacts on smart campus operational efficiency. Through case studies and network simulations, this article offers a novel contribution to adaptive digital security design.